Brain Tumor Microenvironment and Angiogenesis in Melanoma Brain Metastases - Trembath, Dimitri G.; Davis, Eric S.; Rao, Shanti; Bradler, Evan; Saada, Angelica F.; Midkiff, Bentley R.; Snavely, Anna C.; Ewend, Matthew G.; Collichio, Frances A.; Lee, Carrie B.; Karachaliou, Georgia-Sofia; Ayvali, Fatih; et al. (Frontiers in Oncology, 2021)
prognostic factors in patients who have undergone craniotomy for melanoma brain metastases (MBM) before 2011 at the University of Pittsburgh Medical Center (UPMC). We have investigated the prognostic or predictive role of these histopathologic factors in a more contemporary craniotomy cohort from the University of North Carolina at Chapel Hill (UNC-CH). We have also sought to understand better how various immune cell subsets, angiogenic factors, and blood vessels may be associated with clinical and radiographic features in MBM. Methods: Brain tumors from the UPMC and UNC-CH patient cohorts were (re)analyzed by standard histopathology, tumor tissue imaging, and gene expression profiling. Variables were associated with overall survival (OS) and radiographic features. Results: The patient subgroup with high TILs in craniotomy specimens and subsequent treatment with immune checkpoint inhibitors (n=7) trended to have longer OS compared to the subgroup with high TILs and no treatment with immune checkpoint inhibitors (ICIs, n=11, p=0.059). Bleeding was significantly associated with tumor volume before craniotomy, high melanoma-specific expression of basic fibroblast growth factor (bFGF), and high density of CD31+SMA- blood vessels. Brain tumors with high versus low peritumoral edema before craniotomy had low (17%) versus high (41%) incidence of brisk TILs. Melanoma-specific expression of the vascular endothelial growth factor (VEGF) was comparable to VEGF expression by TILs and was not associated with any particular prognostic, radiographic, or histopathologic features. Gene signatures associated with gamma delta (gd) T cells were significantly higher in intracranial than same-patient extracranial metastases and primary melanoma. However, gdT cell density in MBM was not prognostic. Conclusions: ICIs may provide greater clinical benefit in patients with brisk TILs in MBM. Intratumoral hemorrhage in brain metastases, a significant clinical problem, is not merely associated with tumor volume but also with underlying biology. bFGF may be an essential pathway to target. VEGF, a factor principally associated with peritumoral edema, is not only produced by melanoma cells but also by TILs. Therefore, suppressing low-grade peritumoral edema using corticosteroids may harm TIL function in 41% of cases. Ongoing clinical trials targeting VEGF in MBM may predict a lack of unfavorable impacts on TIL density or intratumoral hemorrhage.